2016
DOI: 10.1177/0954407015619505
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of driveline vibrations caused by ageing the limited slip coupling

Abstract: The prediction of the wet-clutch service life still remains a challenge for scientists and engineers. Previous research has shown the significance of the wet-clutch friction characteristics on the driveline dynamics. To avoid driveline vibrations an increasing friction coefficient with increasing sliding speed is desirable. Consequently, prediction of the occurrence of driveline vibrations relies on a detailed knowledge of how the friction characteristics are affected by wet-clutch degradation, as well as an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Negative damping was introduced into the powertrain system because of the negative gradient of μ v characteristic, which made the powertrain system unstable and more prone to start-up judder. Similar conclusions about the start-up judder mechanism can be found in the works of Berglund et al, 5 Crowther et al, 6 and Shin et al 7 However, none of these references had explained the process of introduction of negative damping. In addition to the negative gradient of μ v characteristic, there are other factors that influence the start-up judder, including external motivation, 8 installation and manufacturing error, 9 and thermal effect.…”
Section: Introductionsupporting
confidence: 76%
“…Negative damping was introduced into the powertrain system because of the negative gradient of μ v characteristic, which made the powertrain system unstable and more prone to start-up judder. Similar conclusions about the start-up judder mechanism can be found in the works of Berglund et al, 5 Crowther et al, 6 and Shin et al 7 However, none of these references had explained the process of introduction of negative damping. In addition to the negative gradient of μ v characteristic, there are other factors that influence the start-up judder, including external motivation, 8 installation and manufacturing error, 9 and thermal effect.…”
Section: Introductionsupporting
confidence: 76%
“…Jarvis and Mills [3] presented clutch judder as a vibration, primarily induced by friction in dry clutches. However, this phenomenon is not only confined to dry clutches as shown by Berglund et al [4]. Centea et al [5][6] showed that clutch take-up judder is influenced by the gradient of coefficient of friction variation with the relative speed at the clutch lining interfaces (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen from equation ( 1) that when the relative speed v is large, g( v) approaches 0, and the influence of the stribeck effect is very small, so equation ( 4) can be approximated to equation (6). When the relative speed is close to the critical speed v s , g( v) approaches 1=e, and the stribeck effect cannot be ignored.…”
Section: Nonlinear Friction Modelmentioning
confidence: 99%
“…When the gradient of the friction coefficient with relative speed is negative, the system's comprehensive damping effect is negative, which can easily cause the system to be unstable and then cause the self-excited judder. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Based on the conclusion, many scholars have concentrated on the influencing factors of clutch friction coefficient. Li et al 23 analyzed the influence of friction materials on clutch judder through the comparative analysis of 18 kinds of frictional lining specimens.…”
Section: Introductionmentioning
confidence: 99%